Perancangan Prototype Aplikasi Mobile Ridesolve untuk Memperbaiki Akses Transportasi Mahasiswa Menggunakan Metode Design Sprint - Afifah, Raihana Cindy; Nabarian, Tifanny; Munir, Sirojul (DBESTI: Journal of Digital Business and Technology Innovation, 2024)
Students at Sekolah Tinggi Teknologi Terpadu Nurul Fikri (STT-NF) encounter challenges in accessing affordable and reliable transportation to and from campus, which complicates their search for convenient and cost-effective transport options. This study aims to develop a mobile application with an intuitive and user-friendly interface to enhance the overall transportation experience for students. Employing the Design Sprint methodology, the research follows a structured process involving understanding, diverging, deciding, prototyping, and validating phases. User requirements were gathered through surveys and interviews, and the prototype was created and tested using Figma. Usability testing utilized the System Usability Scale (SUS). The outcome of this study is RideSolve, a mobile app prototype featuring functionalities such as ride booking, driver selection, and ride history viewing. Usability testing revealed a high SUS score of 82, indicating positive user reception and effective fulfillment of their needs. Ultimately, the RideSolve prototype is anticipated to notably enhance transportation convenience for STT-NF students by offering a dependable and user-friendly solution.